1972
DOI: 10.1002/1097-0142(197212)30:6<1588::aid-cncr2820300626>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell myeloma. An interpretive review

Abstract: Melphalan (M), cyclophosphamide (Cy), and BCNU are effective in the treatment of myeloma, producing objective improvement in a direct manifestation of the disease in 35 to 50% of patients, and prolonging survival to approximately 20 months from the start of therapy. Procarbazine is also effective, but the toxicity of prednisone for myeloma cells is questioned. Since the average myeloma tumor‐doubling time is about 6 months, the improved survival of myeloma patients associated with M treatment can be explained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We chose cyclophosphamide (CTX), an alkylating agent without cross‐resistance to melphalan, with a well‐established activity in MM . A series of clinical trials performed in the UK in the 1980s demonstrated the equivalent efficiency of cyclophosphamide compared to melphalan with a favorable toxicity profile, with less profound myelosuppression, making it safe to use in patients eligible for transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…We chose cyclophosphamide (CTX), an alkylating agent without cross‐resistance to melphalan, with a well‐established activity in MM . A series of clinical trials performed in the UK in the 1980s demonstrated the equivalent efficiency of cyclophosphamide compared to melphalan with a favorable toxicity profile, with less profound myelosuppression, making it safe to use in patients eligible for transplantation .…”
Section: Introductionmentioning
confidence: 99%